RELEVANSI NILAI INFORMASI MODAL INTELEKTUAL STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - aria ganna henryanto (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2017)
This research is a replication of Ferraro and Veltri research using some adjustments. The industry chosen in this research is the banking industry with several considerations. The banking industry is a tightly regulated, competitive industry and is a very dominant type of service industry using knowledge assets in the provision of its services (Calistri et al, 2011). The banking industry is also the most sensitive industry to the development of derivative products of science in the era of information technology and human resource assets. The use of information technology as one form of intellectual capital in the banking industry affects the efficiency of service provision of the banking industry today. The results show consistent results with the research of Swartz et al (2006), Wang (2008) Ferraro and Veltri (2011) and Liu et al (2009). Efficient use of the company's physical and financial capital can improve company performance and ultimately affect firm value (Swartz et al, 2009).